Answer:
107
Step-by-step explanation:
x=180-73
x=107
hope it helps
Answer:
0.44444444444
Step-by-step explanation:
Answer:
The choice three ;
![y = 3x + 12](https://tex.z-dn.net/?f=y%20%3D%203x%20%2B%2012)
Step-by-step explanation:
![- 6x + 2y = 24 \\ 2y = 24 + 6x \\ \\ y = \frac{24 + 6x}{2} \\ \\ y = \frac{24}{2} + \frac{6x}{2} \\ \\ y = 12 + 3x](https://tex.z-dn.net/?f=%20-%206x%20%2B%202y%20%3D%2024%20%5C%5C%202y%20%3D%2024%20%2B%206x%20%5C%5C%20%5C%5C%20y%20%3D%20%5Cfrac%7B24%20%2B%206x%7D%7B2%7D%20%20%20%5C%5C%20%20%5C%5C%20y%20%3D%20%20%5Cfrac%7B24%7D%7B2%7D%20%20%2B%20%20%5Cfrac%7B6x%7D%7B2%7D%20%20%5C%5C%20%20%5C%5C%20y%20%3D%2012%20%2B%203x)
<span>Simplifying
12 + -6(w + -3) = 3(-5 + -3w) + 21
Reorder the terms:
12 + -6(-3 + w) = 3(-5 + -3w) + 21
12 + (-3 * -6 + w * -6) = 3(-5 + -3w) + 21
12 + (18 + -6w) = 3(-5 + -3w) + 21
Combine like terms: 12 + 18 = 30
30 + -6w = 3(-5 + -3w) + 21
30 + -6w = (-5 * 3 + -3w * 3) + 21
30 + -6w = (-15 + -9w) + 21
Reorder the terms:
30 + -6w = -15 + 21 + -9w
Combine like terms: -15 + 21 = 6
30 + -6w = 6 + -9w
Solving
30 + -6w = 6 + -9w
Solving for variable 'w'.
Move all terms containing w to the left, all other terms to the right.
Add '9w' to each side of the equation.
30 + -6w + 9w = 6 + -9w + 9w
Combine like terms: -6w + 9w = 3w
30 + 3w = 6 + -9w + 9w
Combine like terms: -9w + 9w = 0
30 + 3w = 6 + 0
30 + 3w = 6
Add '-30' to each side of the equation.
30 + -30 + 3w = 6 + -30
Combine like terms: 30 + -30 = 0
0 + 3w = 6 + -30
3w = 6 + -30
Combine like terms: 6 + -30 = -24
3w = -24
Divide each side by '3'.
w = -8
Simplifying
w = -8</span>
Answer:
16 apples
Step-by-step explanation:
18-2=16